Pengaruh Minat dan Kemandirian Belajar Terhadap Hasil Belajar Matematika Siswa di Kelas VII MTsS TI - Fajri, Fauzan; Isnaniah, Isnaniah; Aprison, Wedra; Rusdi, Rusdi (Lembaga Yasin AlSys, 2025)
The low student mathematics learning outcomes are caused by several problems, namely the low interest and independence of student learning which is the driving force for conducting this research. Ex Post Facto research using quantitative techniques is this type of research. The research population was 118 class VIII MTsS TI Candung students. The instrument used was a questionnaire on interest and independence in learning. The research results produce a regression equation Y= 11.683 + 0.498 representing interest in learning on learning outcomes. t count = 3.113 > t table = 2.052 is the result of the regression significance test. Interest in learning has a fairly large partial influence on mathematics learning outcomes. Y= 16.171 + 0.525 is the regression equation for learning independence on learning outcomes. After carrying out the regression significance test, it was obtained that t = 2.472 > t table = 2.052. Partially, learning independence has a significant effect on mathematics learning outcomes. The resulting multiple regression equation has a determinant coefficient KD = 38.247% and a correlation coefficient value of 0.618 indicating a moderate relationship. The multiple regression significance test produces calculated F = 13.031 > F table = 3.37. It is known that interest and independence have a big influence on mathematics learning outcomes.